Analysis of roof thermal performance with innovative technology - Alchapar, Noelia Liliana (2021)
The roof is the surface most exposed to solar radiation in a home, therefore evaluating the thermal performance of different roofing technologies can significantly improve the building´s thermo-energetic behavior. This work presents an experimental study that analyzes the thermal behavior of a single-family home that modifies the roof surface properties. Comparison of the thermal performance of the house is made under two roof solutions: (i) base case presents an albedo of 0.49 and thermal emissivity of 0.25; (ii) optimized case presents a cladding with smart technology that incorporates bituminous gas microspheres to its composition in addition to being a material with cool characteristics, albedo of 0.85 and thermal emissivity of 0.90. During the evaluated summer period, the optimized roof solution shows a more efficient thermal performance than the base roof. Optimized roof achieves drops of up to 18°C in the outdoor surface temperature and up to 5°C in the indoor surface temperature, while the indoor air temperature go down to 3°C.